العنف ضد المرأة دراسة میدانیة في مدینة بغداد / الكرخ - أ.م. كوثر عبد الحمید سعید (College of Education for Women, 2019)
Violence can be identified as an outreaching on others' dignity, freedom, properties, and life. Therefore, violent actions cannot be determined only on materialistic attacks such as killing, beating, robbery, rape, and civil wars, but it also includes the verbal attacks such as insult, threat, and cursing. Violence against women can be identified as any bad actions that are done against women, which lead to a physical or psychological harm, and invade their safety and freedom whether these actions come from men or women, against one woman or a group of women in special and general places. Before, the social, historical and lawful manners concentrated on sexual distinction between the men and a woman, which, later on, leads to a womanish revolution in the sixties of the last century. This produced an international womanish movement that aimed to destroy focusing on masculinity in society. This research includes eight chapters. The first chapter deals with the conceptual and methodical framework. Chapter two is about the past studies. While chapter three deals with violence against women as a violation to human rights. Chapter four talks about what human beings inherit from social traditions that strengthen violence against women. Then in chapter five, we have the types of violence and its different and famous forms in societies. In chapter six there is analysis to the reasons of violence. While chapter seven talks about violence in Iraq. And finally, there is a practical study which includes a list of information applied on five women who are molested to violence and visit Al- Karkh court. Also, in this research, I depended on the method of case study, where I have chosen five cases of women who suffer from violence from different regions in Baghdad. Their case shows how family violence humiliates woman and subjects her to man's authority, without having any social and legislative protection to protect woman in society.